2014
DOI: 10.4314/tjpr.v13i5.6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Developmental Toxicity of Epidermal Growth Factor using Embryonic Stem Cell Test

Abstract: Purpose: To determine whether epidermal growth factor (EGF) is involved in reproductive developmental toxicity, using the embryonic stem cell test (EST), as well as ascertain how EGF influences embryonic development. Methods: To predict developmental toxicity on the basis of reducing cell viability and inhibition of differentiation of embryonic stem cells, EST was used to assess changes in different blastodermic genes and expression of proteins including ectodermal-specific genes Pax6, NF-H and glial fibrillar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…29 Several reports discussed the toxicity of excessive EGF levels both for in vitro and in vivo studies. 27,30,31 In particular, the report by Ramineni and coworkers successfully demonstrated that a concentration regime between 1-5 ng mL −1 EGF provided maximal cell migration, cellular differentiation and wound healing. 32 Similar EGF levels were attained after 72 hours in our case; hence, this time point was chosen for the following in vitro investigations.…”
Section: Biomaterials Science Papermentioning
confidence: 99%
“…29 Several reports discussed the toxicity of excessive EGF levels both for in vitro and in vivo studies. 27,30,31 In particular, the report by Ramineni and coworkers successfully demonstrated that a concentration regime between 1-5 ng mL −1 EGF provided maximal cell migration, cellular differentiation and wound healing. 32 Similar EGF levels were attained after 72 hours in our case; hence, this time point was chosen for the following in vitro investigations.…”
Section: Biomaterials Science Papermentioning
confidence: 99%